The effects of learning style preferences on performance in learning which utilities print-based open learning materials - Abdullah, Syaharom (Universiti Utara Malaysia, 1999)
This study examines the effects of learning style preferences on the performance in learning utilizing print-based distance learning materials. The experimental design was conducted in which 123 randomly selected UUM students were involved. The subjects were asked to study a chapter, which has been converted into distance learning format, taken from the textbook for their business report writing course. The subjects were tested on their mastery of the content of the chapter after one week. The learning style preferences of the subjects were determined using an instrument developed by Reid (1987). The study has found that the learning style preferences of the subjects are different from that found by an earlier study.The influence of the learning experience is speculated to be the cause. Contrary to the hypothesis, which hypothesis a positive relationship between learning style preferences and learning outcome, the analytical results obtained indicate that only the performance of the three levels of auditory learning style preference are significantly different. To the extent of its reliability, the finding has significant implication for educators in view of the needs to teach more with limited resources. The study, however, is rather limited in scope and a more extensive study is suggested to produce more reliable observations.